The Influence Of Leverage, Earnings Persistence, And Firm Size On Earnings Responses Coeffient In Infrastructure Companies At Bei 2018 – 2021 - Mohamad Zulman Hakim; Yayah Rohaeti; Hesty Erviani Zulaecha; Dewi Rachmania; Januar Eky Pambudi; Budi Rohmansyah (International Journal of Economics, Business and Innovation Research, 2022)
The aim of this research is to examine the leverage, earnings persistence and firm size on the earnings response coefficient (ERC) in infrastructure companies listed in Indonesia Stock Exchange. This research used 16 listed infrastructure companies in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2018 until 2021. Data were analyzed using panel data regression method. The result of the analysis indicated that leverage, earnings persistence does not have a negative effect on the earnings response coefficient (ERC), firm size has a positive effect on the earnings response coefficient. Companies that have a large number of assets are large companies that are considered to have less risk, because large companies are considered to have more access to capital, so that the company has the flexibility and ability to obtain funds.